SISTEM PAKAR BERBASIS ANDROID UNTUK DIAGNOSIS PENYAKIT BALITA PADA USIA NEONATAL - Saputra, Ricco Herdiyan; Baba, Jimi Ali; Kesuma, Mezan el-Khaeri (Institut Teknologi dan Bisnis Diniyyah Lampung, 2021)
According to the Minister of Health of the Republic of Indonesia, the number of under-five deaths in 2020 is 28.2 thousand cases. This study was conducted to more easily get information about the types of diseases in toddlers. The method in this study uses the Weighted Product method with seven criteria from observations. Apart from the 7 criteria, there is also a weight criterion value in toddlers that also determines the disease. This research uses the current technology often used by the community, namely Android. Android as a user interfaces in performing calculations using the Weighted Product method. The process of performing alternative calculations exists as the most significant value with a value of 0.123, so the results of the calculation of disease in toddlers 9 are toddlers who suffer from many diseases.